Designing Arabic Interactive Courseware for Enhancing Writing Skills: Self-Learning Prototype Among Non-Arabic Speakers in IIUM - Sahrir, Muhammad Sabri; Ahmed Mahmoud, Ahmed Ragheb; Md Ghalib, Mohd. Feham (US-China Education Review A, 2015)
The use of modern technology in the process of teaching and learning the Arabic language has a very important role in developing student's performance and improving his four language skills at all levels of learning. The students of non-native Arabic speakers are in the high need to use modern technology in language learning, that contribute to the development of the four basic language skills, since they are living outside from the original Arabic environment. This technology contributes to the creation of an artificial environment to learn a second language among these students. With regard to the process of learning the Arabic language by using modern technology in Malaysia, it has attracted academic discussions research by various researchers and experts in this area, such as discussed by Muhammad Feham and Isarji (2000), Zawawi (2008) and Ashinida Aladdin, et. al. (2008) on the issue of the lack of use of Arabic language teachers for modern instructional technology, Ashinida Aladdin, et. al. 2008), while (Muhammad Feham (2006) on the other hand has raised the issue of the lack of innovation of modern technology in teaching Arabic language. However, we find that there are several attempts to invent more modern technologies in teaching Arabic language in Malaysia such as the design of computer language games in learning Arabic (Muhammad Sabri (2011) , the use of E-Portfolio in Arabic language learning (Muhammad Firdaus (2012) and Virtual Tutor (Ahmed Ragheb (2013). Consequently, this research seeks to study the possibility of designing and developing a prototype that specializes in improving writing skill in Arabic language for non-native speaker through a program that is considered as flexible and interactive. The program is expected to enhance learners’ self-motivation and improve their language skills by self-monitoring common writing errors done by Malaysian students. The design of such an interactive program aims to develop Arabic writing skill and eventually to evaluate this program among students for further improvement in the future. This program is specifically designed to identify and to correct morphological errors by using Microsoft Word program via a special font known as ‘Modaqqeeq Sarfiy’ (morphological checker). This research is carried out via phases of ‘ADDIE’ model in the design and development of this prototype among the students who specialize in Arabic language as they are studying a course for computer applications in language and literature in International Islamic University Malaysia. The result of this study has indicated high mean scores among learners to this interactive spelling checker, beside suggestions and comments forwarded by them to improve the program for its future development. This research has definitely stressed on the importance of using advanced and new emerging technologies as a mean to enhance the teaching of Arabic language to non-native speakers especially in the four language skills. Ironically, language accuracy and fluency depends on the development and the spirit of various changing of modern technologies.